Approaches and methods in language teaching (A description and analysis) - Jack C Richards (Cambridge Univ. Press, 1986)
The book presents an overview and analysis of the major approaches and methods used in second and foreign language teaching. The methods and approaches covered include: Grammar translation; the Direct method; Situational language teaching; Audiolingualism; Communicative language teaching; the Silent way; Community language learning; Total physical response; the Natural approach; Suggestopedia